SAT0522 PROGRESSION OF VISION-RELATED QUALITY OF LIFE AND IDENTIFICATION OF RISK FACTORS IN NON-INFECTIOUS UVEITIS PATIENTS. (2nd June 2020) - Hernandez, I.; Abasolo, L.; Fernandez, B.; Madrid García, A.; Font, J.; Pato, E.; Rodriguez Rodriguez, L.
Abstract : Background: Uveitis are characterized by inflammation of the middle layer of the eye wall. In developed countries uveitis are the second major treatable cause of blindness in those 20–65 years of age. Additionally, more than 50% of the subjects affected with these conditions will develop complications related to the uveitis, and more than 30% will suffer visual impairment. As a result, these conditions are associated with an important burden. The assessment of the patient's quality of life (QoL) through standardized and validated questionnaires allows us to evaluate objectively the burden of the disease. Several studies have shown that the QoL of uveitis patients is reduced when compared with that of general population. Moreover, several socio-demographic and clinical related characteristics have been associated with impaired QoL. However, no longitudinal analysis of the vision-related (VR) QoL in clinical practice has been carried out. Objectives: To describe VR-QoL in non-infectious uveitis (NIU) patients during a follow-up period of two years. Furthermore, to analyse the influence of socio-demographic, clinical and treatment factors on the progression of VR-QoL. Methods: Longitudinal prospective study which includes patients examined in a multidisciplinary tertiary uveitis clinic, with a diagnosis of NIU. In each of these patients a yearly determination of VR-QoL was carried out following the VFQ-25 questionnaire, finally including all those who had completed at least an initial questionnaire and a second one after two years of follow-up. Analysis of risk factors at baseline in repeated VFQ-25 measurements was carried out by generalized estimating equations (GEE) models. Variables related to demographic, clinical and treatment factors with a determination of p-value <0.15 were included in multivariable models, which were then compared using the Quasi Akaike Information Criteria (qAIC). A local Ethics Committee approved the execution of this project. Results: 128 patients were included, 117 of which also had an evaluation after the first year of follow-up. 55.5% were female with a median age of 34 years at the start of symptoms and of 37 years at the moment of attending our clinic for the first time. First evaluation of VR-QoL was determined a median (p25-p75) of 6.1 (1.8-13.1) years after that first visit. The most frequent locations of NIU were anterior (41.1%), panuveitis (27.4%), posterior (16.1%) and intermediate (15.3%). At our first evaluation, 27.3% of patients were receiving treatment with topical steroids, 22.3% oral, 49.2% immunosuppressant drugs (both synthetic and/or biological) and 19.05% biological therapies. The median (p25-p75) VFG25 determinations at baseline, first and second years of follow-up were 0.87 (0.78-0.93), 0.88 (0.80-0.93) y 0.89 (0.81-0.94), with no significant differences (first year vs. Baseline p = 0.54; 2 years vs. Baseline p = 0.61). In the GEE multivariable models the presence at baseline of permanent incapacity due to NIU, concomitant thyroid disease, worse visual acuity, unilateral pattern, cataracts, retinal vasculitis, epiretinal membrane and use of azathioprine were independently associated with a worse VR-QoL (Table 1 ). Conclusion: During these two years of follow-up, no significant changes have taken place regarding VR-QoL in patients with NIU assessed at a tertiary centre. Other than visual acuity at baseline, certain ocular manifestations and clinical comorbidities have also been shown to have an independent effect on the VR-QoL of these patients. Disclosure of Interests: None declared